2022
DOI: 10.1111/ocr.12580
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity of palatal volume and surface area in various malocclusions

Abstract: The complex and multifactorial aetiology of malocclusion reflects the interplay between predominantly genetic factors and environmental influences. 1,2 The latter include localized effects in response to sustained impactful insults such as mouth breathing, sucking habits and abnormal swallowing and tongue activity. 3 The more commanding 'genetically determined' functions in the craniofacial complex (e.g. brain growth, respiration and muscle activity) are thought to direct the growth of the craniofacial skeleto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…In skeletal Class subjects, both males and females, hyperdivergent subjects had a higher and narrower palate than hypodivergent subjects, which was consistent with the results of previous studies [8,11,[17][18]. Palaoni et al used GMM method and found that the vertical patterns had the greatest in uence on the palatal morphology in skeletal Class III subjects, and as the mandibular plane angle increased, the palate became higher and narrower [11].…”
Section: Comparison Of 3d Palatal Morphology With Different Vertical ...supporting
confidence: 83%
“…In skeletal Class subjects, both males and females, hyperdivergent subjects had a higher and narrower palate than hypodivergent subjects, which was consistent with the results of previous studies [8,11,[17][18]. Palaoni et al used GMM method and found that the vertical patterns had the greatest in uence on the palatal morphology in skeletal Class III subjects, and as the mandibular plane angle increased, the palate became higher and narrower [11].…”
Section: Comparison Of 3d Palatal Morphology With Different Vertical ...supporting
confidence: 83%